Epigraphy, philology, and the hebrew bible : methodological perspectives on philological and comparative study of the hebrew bible in honor of Jo Ann Hackett - Pat-El, Na‘ama (2015)
Fil: Hutton, Jeremy M. University of Wisconsin–Madison; Estados Unidos